RELASI KUASA UNMET NEED DALAM PENGAMBILAN KEPUTUSAN KELUARGA BERENCANA: Studi di Kecamatan Gondomanan Kota Yogyakarta - SARI, FESTIKA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
There was a new paradigm of the National Family Planning Program from the population control and fertility decline approach to reproductive health approach to reproductive rights and gender equality concern. The new concept of reproductive health had more widespread care, such as the fulfillment of reproductive health of individuals, both men and women throughout their life cycle, including women's reproductive rights, gender equality and issues of responsibility of men in reproductive health, including family plannings. This research aimed to figure out the dynamic gender of unmet need affected the condition of unmet need in Kelurahan Prawirodirjan, Gondomanan District, of Yogyakarta Municipality. The specific aims were to determine the condition of unmet need and gender relations of unmet need influenced the condition of unmet need in Kelurahan Prawirodirjan, Gondomanan District, of Yogyakarta Municipality. Qualitative approach was used for this research with the method of case study. The data collection method was done by triangulation by combining multiple data collection techniques such as interviews, observation and documentation. Data were taken by purposive sampling based on to the criteria desired. The results showed that most of unmet need in the Kelurahan Prawirodirjan, Gondomanan District were older age groups between 30-49 years old. The highest number was coming from not wanting child any more group ( TIAL ). Unmet need had a small number of family members and the spacing of each child was far enough. This was appropriate with the norm of two childs are enough. The involvement of men were lack. Husband's participation in family planning was indirect participation. There was still wives who had understanding that the use of birth control is the their obligation, even higher levels of education of wives do not make understanding change. However, the wives already had bargaining power to negotiate their desire toward their husbands. The attitude of not using contraception were rooted from wives's rejection of using contraception. Wives's rejection to use contraceptives due to their fear of side effects, post-natal trauma and health risks from the use of contraception. Key words: unmet need, power relation, family planning